Productivity Potential of Promising Sugarcane Clones (UMG.NX) In Second Ratoon On Alluvial Soil - Setya Maulina Primayunita; Setyo Budi; Wiharyanti Nur Lailiyah (UNIVED Press, Dehasen University Bengkulu, 2025)
Purpuse: This study aims to reevaluate the productivity of seven promising sugarcane (Saccharum officinarum L.) clones on alluvial land in the second harvest. Domestic sugar demand continues to increase, along with an imbalance in sugar production, leading to Indonesia's continuing reliance on sugar imports. The decline in sugarcane productivity is attributed to genetic degeneration of varieties and limited availability of superior varieties. The availability of new superior varieties with high productivity and high yield is one way to increase sugar production. Methodology: The experimental method used a one-factor randomized block design (RBD) with nine treatments. The treatments consisted of seven superior sugarcane clones (UMG.NX) and two commercial varieties as controls (PS 881 and Bululawang). Data analysis used one-way ANOVA (n = 3 replications for each retreatments), and differences between treatments were tested with LSD (α = 0.05), correlation, and heritability. Results: The results confirmed that the superior UMG.NX clones had high productivity (brix, weight, yield, and sugar content) in ratoon cultivation on alluvial land. Findings: The SB19 UMG.NX clone has a brix level of 24.33±0.588% and a yield of 9.59±0.486%, which is significantly different (p<0.05) from the control. The SB19 UMG.NX, SB20 UMG.NX, and JW 01 clones showed high productivity (sugar cane weight, yield, and sugar content). Novelty: All parameters were strongly and positively correlated, and the heritability values for sugarcane productivity were in the high category (brix: 0.82; sugarcane weight: 0.94; yield: 0.74; fiber: 0.94). Originality: These superior clones have the potential to be developed into new superior varieties (NSVs) and contribute to sugar supply resilience. Conclusion: The decline in sugarcane productivity is attributed to genetic degeneration of varieties and limited availability of superior varieties. The availability of new superior varieties with high productivity and high yield is one way to increase sugar production. . Type of Paper: Identifies the type of a research